TEACHER’S PEDAGOGICAL COMPETENCE IN TEACHING ENGLISH AT EXCELLENT CLASS VIII IN JUNIOR HIGH SCHOOL - Pipit Ertika Daristin; Nailah Maziyah (J-Shelves of Indragiri (JSI), 2025)
In education, the role of the teacher determines the quality of learning, especially for teachers who teach English as a Foreign Language (EFL). This study aims to know the pedagogical competence of English teacher in manage the English classroom, and how the teacher evaluates the learning process in class at junior high school class VIII in Jombang, East Java. This study used a qualitative case study. The subject of this research is one English teacher of excellent class VIII in Junior High School. There were two kinds of instruments in this research: interview and class observation. This study concluded that English teachers demonstrate good pedagogical competence in classroom learning. Based on the result of the observation, the teacher showed the application of pedagogical competence during the teaching process. In managing the English classroom, the teacher can effectively manage the classroom by creating structured lesson plans and following them throughout the class. In evaluating the learning process shows that the teacher uses various methods and techniques to evaluate the learning process comprehensively and variously in evaluating the learning process.